MANAJEMEN PROGRAM GATOT KACA (GERAKAN TOTALITAS AKSI BACA) DALAM PENGUATAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Intan Nurunnahar; Lina Marlina; Veni Oktaviani; Ricky Rosadi; Dinny Mardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education is an important aspect of educational practice that can be strengthened through a literacy-based school culture. One of its implementations at SD Negeri 3 Selaawi, Pasawahan District, is the (GATOT KACA) Program Gerakan Totalitas Aksi Baca, which is carried out as part of the Salasa Mapag Buana activity within the 7 Poe Atikan Purwakarta Istimewa policy. This study aimed to analyze the management of the GATOT KACA Program in strengthening students’ character. The study employed a qualitative approach using a case study method. George R. Terry’s management theory was used as the analytical framework. Research participants included the principal, teachers, and students. Data were collected through observation, semi-structured interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the GATOT KACA Program was implemented through planning, organizing, actuating, evaluating, and controlling processes involving the principal, teachers, students, and parents. Supporting factors included the commitment of school members, the availability of literacy facilities, teacher involvement, and parental support. Meanwhile, inhibiting factors included differences in students’ reading abilities, uneven reading interest, gadget use, limited reading materials, and limited implementation time. The program contributed positively to the development of students’ discipline, responsibility, self-confidence, curiosity, and cooperation. Therefore, the GATOT KACA Program can serve as an effective literacy-based school culture strategy for strengthening students’ character in elementary schools. Keywords: GATOT KACA Program, literacy culture, character education, student character, elementary school.